Aquinas’ philosophical critique of philosophy - Lehrberger, James (Verbum – Analecta Neolatina, 2004)
Down through the ages different philosophers, whatever their other disagreements, have insisted that the philosophic life is the best human life. As philosophers, they equate happiness with wisdom, the comprehensive account of the whole of reality in light of its first principles and causes. In his Expositio super librum Boethii de trinitate, Thomas Aquinas denies this teaching. He asserts, rather, that philosophy can know with absolute certainty that it cannot attain such wisdom and thus that it cannot be the best life. More precisely, Thomas argues that the limited abstracting power of the agent intellect precludes in principle the very possibility of a quod est knowledge of the First Principle of the whole; human beings must resign themselves to a mere quia knowledge of it at best. On the other hand, the philosophers are right to identify happiness with wisdom; but the very impossibility of attaining that wisdom negates the claims that philosophy provides the best and happy life. Thomas, in short, turns the philosophers own arguments against themselves. He discovers the roots of the philosophers erroneous account of the best life in their now disproved assumption that the human mind is commensurate with reality itself.